Peroxynitrite and 4-Hydroxynonenal Inactivate Breast Cancer Resistance Protein/ABCG2. (21st January 2019) - Verenich, Svetlana; Gerk, Phillip M.
Abstract : Oxidative stress may arise from a variety of pathologies and results in the formation of toxic and reactive chemical species. Extensive research has been done to establish mechanisms of formation and cytotoxic effects of a number of different products of oxidation stress including peroxynitrite (PN) and 4-hydroxynonenal (4HNE). However, relatively few studies have investigated their effects on ATP-binding cassette (ABC) transporters. The objective of this investigation was to determine the effects of PN and 4HNE on BCRP/ABCG2. To eliminate the effect of metabolic enzymes, the experiments were carried out with inside-out Sf9 membrane vesicles overexpressing BCRP/ABCG2 using riboflavin as a substrate. The experiments revealed that PN produced IC50 of about 31.2 ± 2.7 μ M, based upon initial concentrations. The IC50 for 4HNE was estimated to be 92 ± 1.4 μ M. Preincubation of membrane vesicles with either PN or 4HNE caused the maximal rate of transport (V m a x ) to drop drastically, up to 19 times, with no or much smaller effect onK m . Thus, PN and 4NE can inhibit BCRP transport activity.